Effect of nutrition counselling with a digital job aid on child dietary diversity: Analysis of secondary outcomes from a cluster randomised controlled trial in rural Bangladesh. Issue 1 (31st August 2021) - Billah, Sk Masum; Ferdous, Tarana E.; Kelly, Patrick; Raynes‐Greenow, Camille; Siddique, Abu Bakkar; Choudhury, Nuzhat; Ahmed, Tahmeed; Gillespie, Stuart; Hoddinott, John; Menon, Purnima; Dibley, Michael John; Arifeen, Shams El
Abstract: Adequate dietary diversity among infants is often suboptimal in developing countries. We assessed the impact of nutrition counselling using a digital job aid on dietary diversity of children aged 6–23 months using data from a cluster randomised controlled trial in Bangladesh. The trial had five arms, each with 25 clusters. The four intervention arms provided counselling using a digital job aid and different prenatal and post‐natal combinations of lipid‐based supplements and the comparison arm with usual practice. We enrolled 1500 pregnant women and followed them until the children reached their second birthday. We developed a tablet‐based system for intervention delivery, data collection and project supervision. We combined the four intervention arms ( n = 855), in which community health workers (CHWs) provided age‐appropriate complementary feeding counselling, to compare against the comparison arm ( n = 403). We calculated the outcome indicators from the children's 24‐h dietary recalls. Overall, the intervention increased the mean dietary diversity score by 0.09 (95% confidence interval [CI]: 0.2–0.16) and odds of minimum dietary diversity by 18% (95% CI: 0.99–1.40). However, there was a significant interaction on the effect of the intervention on dietary diversity by age. The mean dietary diversity score was 0.24 (95% CI: 0.11–0.37) higher in the intervention than in the comparison arm at 9 months and 0.14 (95% CI: 0.01–27) at 12 months of age. The intervention effect was non‐significant at an older age. Overall, consumption of flesh food was 1.32 times higher in the intervention arm (odds ratio [OR] 1.32, 95% CI: 1.11–1.57) in 6–23 months of age. The intervention significantly improved child dietary diversity score in households with mild and moderate food insecurity by 0.27 (95% CI: 0.06–0.49) and 0.16 (0.05–27), respectively, but not with food‐secure and severely food‐insecure households. Although the study did not evaluate the impact of digital job aid alone, the findings indicate the utility of nutrition counselling by CHWs using a digital job aid to improve child feeding practices in broader programmes.